Consumers’ Consideration of Functional Utility when Choosing Major Household Appliances - Donoghue, Suné; Erasmus , Alet C; Sonnenberg , Nadine (Nurture, 2011)
This research investigated consumers’ consideration of product attributes concerning their choice of major household appliances to explicate the pertinence of functional attributes versus other concerns such as environmental issues and status-bearing factors. A cross-sectional survey was performed amongst middle- to upper-income households in Tshwane, South Africa. The sample (N = 446) consisted of 69.4% females and 30.6% males who were further distinguished in terms of age, income and level of education. Exploratory factor analysis revealed consumers’ attention to seven factors, of which functionality and durability aspects seemed more prevalent. A stronger concern for functional attributes compared to status factors and environmental issues confirms a need for the provision of product information that would enhance informed buying decisions, minimize consumers’ functional risk perception and reduce negative post-purchase judgments.